Spin switching in antiferromagnets using Neel-order spin-orbit torques - Wadley, P.; Edmonds, K.W. (Chinese Physical Society and IOP Publishing Ltd, 2018)
Antiferromagnets offer considerable potential for electronic device applications. This article reviews recent demonstrations of spin manipulation in antiferromagnetic devices using applied electrical currents. Due to spin-orbit coupling in environments with particular crystalline or structural symmetries, the electric current can induce an effective magnetic field with a sign that alternates on the lengthscale of the unit cell. The staggered effective field provides an efficient mechanism for switching antiferromagnetic domains and moving antiferromagnetic domain walls, with writing speeds in the terahertz regime.